Tax Evasion and Self-Employment in a High-Tax Country: Evidence from Sweden - Per Engström; Bertil Holmlund (Uppsala University, Department of Economics, 2006)
Self-employed individuals have arguably greater opportunities than wage earners to underreport their incomes. The incentives for underreporting should be especially strong in an economy with generally high taxes. This paper uses recent income and expenditure data to examine the extent of underreporting of income among self-employed individuals in Sweden. A key hypothesis is that underreporting of incomes among the self-employed would be visible in the data as excess food consumption, for a given level of observed income. Our results confirm the underreporting hypothesis. In particular, we estimate that households with at least one self-employed member underreport their total incomes by around 30 percent. Under-reporting appears to be twice as prevalent among self-employed people with unincorporated businesses as among those with incorporated businesses.
urn:nbn:se:uu:diva-83086
Keywords: D12; H24; H25; H26; 330; Tax evasion; self-employment; Engel curves; Steuerflucht; Selbstständige; Mikroökonomische Konsumfunktion; Schweden